2014
DOI: 10.1111/tri.12341
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic differences between phenotypes of chronic lung allograft dysfunction after lung transplantation

Abstract: Distinct phenotypes of chronic lung allograft dysfunction (CLAD) after lung transplantation are emerging with lymphocytic bronchiolitis (LB)/azithromycin reversible allograft dysfunction (ARAD), classical or fibrotic bronchiolitis obliterans syndrome (BOS), and restrictive allograft syndrome (RAS) proposed as separate entities. We have additionally identified lung transplant recipients with prior LB, demonstrating persistent airway neutrophilia (PAN) despite azithromycin treatment. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
(50 reference statements)
4
39
0
Order By: Relevance
“…As previously described [14], the RAS phenotype (represented in 32% of CLAD development in the study group) is characterized by fibrotic areas that may be the result of the increased levels of IL-1Ra in the study group. In the recent study from Suwara et al, patients with persistent airway neutrophilia also demonstrated an increase in IL-1α and IL-1β [15], however no survival analysis was performed and limited cytokines were investigated compared to our study. Cytokine analysis and COX proportional hazards model demonstrated that the inflammatory mechanism in our study is possibly IL-1β mediated, which may open new perspectives for future therapies.…”
Section: Discussionmentioning
confidence: 81%
“…As previously described [14], the RAS phenotype (represented in 32% of CLAD development in the study group) is characterized by fibrotic areas that may be the result of the increased levels of IL-1Ra in the study group. In the recent study from Suwara et al, patients with persistent airway neutrophilia also demonstrated an increase in IL-1α and IL-1β [15], however no survival analysis was performed and limited cytokines were investigated compared to our study. Cytokine analysis and COX proportional hazards model demonstrated that the inflammatory mechanism in our study is possibly IL-1β mediated, which may open new perspectives for future therapies.…”
Section: Discussionmentioning
confidence: 81%
“…That report suggested that an early chemotactic signal for monocytes and lymphocytes was present in lungs with PGD and that the activated endothelial or epithelial surfaces may have contributed to that signal. Notably, despite observations that cultured bronchial epithelial cells isolated from chronically rejected lung transplant recipients produced high amounts of inflammatory mediators, 18 it remains to be determined whether bronchial epithelium plays a direct role in IRI-mediated cytokine production in PGD patients.…”
Section: Epithelium and Endotheliummentioning
confidence: 99%
“…These patients usually present with a colonized graft (mostly pseudomonas) and demonstrate inferior survival compared to patients without neutrophilia (38). Interestingly, IL-1α is increased in BAL of those patients indicating that these alarmins might play an important role in the pathophysiology of BOS (39). Macrolide treatment does not seem to affect these patients (40).…”
Section: Treatmentmentioning
confidence: 99%